Penerapan Model ASSURE Menggunakan Aplikasi Buku Saku Digital Melalui Website dalam Pembelajaran Teks Berita pada Peserta Didik Kelas VII SMP - Annisa Wahyu Palupi; Istiqbalul Fitriya; Khatim Laela; Virda Eka Pratiwi; Yun Nur Aeni; Asep Purwo Yudi Utomo; Diyamon Prasandha (CV. Aksara Global, 2023)
Learning Indonesian contains material regarding news texts that students need to master. Based on observations at SMP N 19 Semarang, especially in class VII F, it shows that learning carried out on news text material has not been carried out effectively, and the material has not been fully conveyed properly in the learning process resulting in learning that cannot be said according to learning outcomes. Educators need to carry out activities to improve learning and deal with problems in the classroom, one of which is by designing learning media that can help facilitate the learning process. This model needs to be integrated with something that is currently closely related to students so that it can provide an imprinted and memorable learning experience for students. One model that is relevant to the characteristics of students is the ASSURE model. Based on the research that was conducted on 32 students at SMP N 19 Semarang, in the first cycle the average student assessment score was below the average score of 69.53, while in the second cycle there was an increase in student assessment scores with an average score. -class average 81.25. This proves that the application of the ASSURE model for digital pocket book learning media to news texts for class VII SMP can be said to be effective.